Evaluation of genetically improved strain of Trichogramma chilonis for the management of sugarcane stalk borer (Chilo auricilius) - SINGH, SATNAM; SHARMA, RAKESH KUMAR; KAUR, PARAMJIT; SHENHMAR, MANINDER (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2003–05 to evaluate augmentative releases of 2 strains of Trichogramma chilonis Ishii, i e Ludhiana (Punjab) and genetically improved high temperature-tolerant strain and mechanical control (removal of water shoots and infested canes at 15 days interval) for the management of stalk borer [Chilo auricilius (Dudgeon)]. Parasitoid strains (high temperature-tolerant strain @ 30 000, 40 000 and 50 000 parasitized eggs/ha, while Ludhiana strain @ 50 000/ha) were released in the form of tricho-cards at 10 days interval from July to October. Twelve releases of high temperature-tolerant @ 40 000 and 50 000/ha and Ludhiana strain @ 50 000/ha checked the borer incidence by 39.05, 55.09 and 51.89%, respectively as compared to control. The recovery of parasitoid using eggs of factitious host Corcyra cephalonica (Stainton) high temperature-tolerant and Ludhiana strain @ 50 000/ha to be more efficient as compared to control and other 2 doses of high temperature-tolerant strain, however, the cost : benefit ratio and yield in high temperature-tolerant strain @ 40 000/ha released plots was comparable to the former two. This was supported by randomly amplified polymorphic DNA (RAPD) markers investigation of genetic variation among T. chilonis strains. The RAPD profiles with 9 primers showed genetic differentiation between both strains of T. chilonis. Thus revealing genetic improvement of biocontrol agents may help in increasing their efficiency at field level but more studies at field level are still required.